Microsurgical Reconstruction of the Mandible in a Patient with Evans Syndrome: A Case Report and Review of the Literature - Bedogni, Alberto; Anesi, Alexandre; Fior, Andrea; Bettini, Giordana; Nocini, Pier Francesco (Journal of Reconstructive Microsurgery, 2013)
In this report, we describe the first successful case of microvascular free tissue transfer in a patient with Evans Syndrome (ES), a rare form of idiopathic thrombocytopenic purpura (ITP) and associated autoimmune hemolytic anemia (AIHA). Microvascular surgery in the setting of ES is likely to have higher complication rates because of the increased risk of postoperative bleeding and free flap thrombosis. The case presented here opens up to the feasibility of microvascular reconstruction of patients with coagulation disorders like ES. Every effort should be made to control for hemolytic, thrombocytopenic, and thrombophilic states associated with ES. In the absence of evidence-based treatment guidelines for ES, personalized treatment protocols with high-dose corticosteroids, immunoglobulin, and postoperative anticoagulation regimen are highly recommended.
Keywords: Evans Syndrome; idiopathic thrombocytopenic purpura; microsurgery; thrombosis; fibula flap